1998
DOI: 10.1063/1.475611
|View full text |Cite
|
Sign up to set email alerts
|

Predissociation of the Na2 3 3Πg and other triplet states

Abstract: The Na2 3 3Πg state adiabatically dissociates to the 3s+4p atomic limit. The 3 3Πg levels below the 3s+3d atomic limit have been observed by perturbation facilitated optical–optical double resonance (PFOODR) fluorescence excitation spectroscopy. Energy levels above the 3s+3d atomic limit cannot be observed by detecting molecular fluorescence but are observable by detecting atomic 3d→3p fluorescence. The 3 3Πg state interacts with the 3s+3d 2 3Πg state. At lower energy this interaction is responsible for many p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…The resulting simulated spectrum possessed a reasonable resemblance with the experimental spectrum [11], although, of course, peaks of the 4 3 R þ g predissociated lines as well as unassigned features were not reproduced. Later [22] additional spectra of the Na 2 2 3 P g $ 3 3 P g $ 4 3 R þ g predissociation were observed and simulated within the similar model and the similar characteristic quality, however, with a quite different computational method of the complex scaling (see [29][30][31]).…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations
“…The resulting simulated spectrum possessed a reasonable resemblance with the experimental spectrum [11], although, of course, peaks of the 4 3 R þ g predissociated lines as well as unassigned features were not reproduced. Later [22] additional spectra of the Na 2 2 3 P g $ 3 3 P g $ 4 3 R þ g predissociation were observed and simulated within the similar model and the similar characteristic quality, however, with a quite different computational method of the complex scaling (see [29][30][31]).…”
Section: Introductionmentioning
confidence: 71%
“…Liu et al [11] reported the first observation of the strong predissociation in the system Na 2 2 3 P g $ 3 3 P g $ 4 3 R þ g . Both 3 3 P g and 4 3 R þ g states dissociate to the 3s + 4p atomic limit, which is about 1100 cm À1 higher than the 3s + 3d dissociation limit of the 2 3 P g state.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…(21) and (22). Natural lithium vapor was generated in a crossed heatpipe with about 1 Torr argon buffer gas.…”
Section: Methodsmentioning
confidence: 99%